STRATEGI MARKETING GLOBAL LUXURY BRAND “LOUIS VUITTON” DALAM VALUE CREATION MELALUI FIGURE KOREAN WAVE - Cut Mauliamala; Adiasri Putri Purbantina (Jurnal Ekonomika dan Bisnis, 2022)
The Korean Wave is a global phenomenon that is currently developing and expanding in the world. As a result of the widespread cultural globalization, it has created an MNC luxury brand company to participate in utilizing Korean Wave figures in marketing and maintaining its brand image. The method they use is to make Korean Wave figures as the company's brand ambassadors. Through the mass of fans, luxury brand companies can trust in the ease of communicating with the world community regarding their products through these Korean Wave figures. This study combines the concepts of Global Marketing Strategy, Value Creation, Value Chain, and Brand ambassador (visibility, credibility, attraction (similarity, physical likability, and non-physical likability), and power) to identify Korean Wave figures who are appropriate in product campaigns. luxury brands. The result of this research is that by utilizing the globalization of the Korean Wave, luxury brand Louis Vuitton companies can easily market and maintain their brand value to global consumers, especially in the Asian market.